2021
DOI: 10.1002/hep.31282
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of Interferon‐α Subtypes Reveals Potent Hepatitis B Virus Suppression by a Concerted Action of Interferon‐α and Interferon‐γ Signaling

Abstract: Background and Aims Interferon (IFN)‐α, composed of numerous subtypes, plays a crucial role in immune defense. As the most studied subtype, IFN‐α2 has been used for treating chronic hepatitis B virus (HBV) infection, with advantages of finite treatment duration and sustained virologic response, but its efficacy remains relatively low. This study aimed to screen for IFN‐α subtypes with the highest anti‐HBV potency and to characterize mechanisms of IFN‐α–mediated HBV restriction. Approach and Results Using cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 42 publications
14
69
0
Order By: Relevance
“…One possibility is that these altered IFNβ-specific genes (such as those that decreased protection from DNA damage) may directly contribute to CD4+ T cell death, in line with previous studies linking IFN-Is and CD4+ T cell depletion [91,92]. Given the predicted pleiotropic effects of IFNβ, our data also raise concerns in utilizing IFNβ for treating chronic Hepatitis B virus infections that became refractory to IFNα treatment [76,93,94]. Notably, IFNβ administered <7 days post-symptom onset may help resolve infection with the novel pandemic coronavirus, SARS-CoV-2 [95].…”
Section: Plos Pathogenssupporting
confidence: 83%
See 1 more Smart Citation
“…One possibility is that these altered IFNβ-specific genes (such as those that decreased protection from DNA damage) may directly contribute to CD4+ T cell death, in line with previous studies linking IFN-Is and CD4+ T cell depletion [91,92]. Given the predicted pleiotropic effects of IFNβ, our data also raise concerns in utilizing IFNβ for treating chronic Hepatitis B virus infections that became refractory to IFNα treatment [76,93,94]. Notably, IFNβ administered <7 days post-symptom onset may help resolve infection with the novel pandemic coronavirus, SARS-CoV-2 [95].…”
Section: Plos Pathogenssupporting
confidence: 83%
“…Our group and others reported diverse antiviral potencies of the IFNα subtypes and IFNβ that correlated with their IFNAR binding properties. These data emphasize the contribution of quantitative differences in IFNAR signaling in controlling acute viral infection [12][13][14][15]76]. However, data from multiple in vivo studies also revealed that the IFNα subtypes may have Expression levels were based on TMM-transformed counts.…”
Section: Discussionmentioning
confidence: 90%
“…The PacBio circular consensus sequencing reads analysed in this study have been previously published and can be found in the European Nucleotide Archive (PRJEB12450) [1]. The RNA-seq libraries of hepatitis B virus (HBV)-positive biopsy samples of human liver tumours and tissues, and portal vein tumour thrombosis (129, 182 and 92 libraries, respectively), and HBV-infected primary human hepatocytes (83 libraries) and human cultured cells HepaRG (4 libraries) and HepG2-NTCP (11 libraries) were downloaded from the Sequence Read Archive [2–18] (see the metadata in Table S1, available with the online version of this article).…”
Section: Data Summarymentioning
confidence: 99%
“…High costs and adverse side effects have also limited the use of IFN-α. Alternatives are being investigated and an iterative approach has led to the identification of new IFNs with increased potency, such as the recently described IFN-α 14[ 203 ].…”
Section: Anti-hbv Epigenetic Therapymentioning
confidence: 99%